2019
DOI: 10.1186/s12933-019-0953-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk of early mortality and cardiovascular disease in type 1 diabetes: a comparison with type 2 diabetes, a nationwide study

Abstract: BackgroundBoth type 1 and type 2 diabetes are well-established risk factors for cardiovascular disease and early mortality. However, few studies have directly compared the hazards of cardiovascular outcomes and premature death among people with type 1 diabetes to those among people with type 2 diabetes and subjects without diabetes. Furthermore, information about the hazard of cardiovascular disease and early mortality among Asians with type 1 diabetes is sparse, although the clinical and epidemiological chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 56 publications
(82 reference statements)
3
59
1
3
Order By: Relevance
“…The endpoint was incidence of hHF. The hHF was defined as the first hospitalization under a primary diagnosis of ICD-10 code I50 as reported in previous studies [23][24][25]. The study population was followed up from baseline (the date of the second health examination between 2013 and 2014) until the date of death, development of hHF, or December 31, 2017, whichever came first.…”
Section: Study Cohort Outcomes and Follow-upmentioning
confidence: 99%
“…The endpoint was incidence of hHF. The hHF was defined as the first hospitalization under a primary diagnosis of ICD-10 code I50 as reported in previous studies [23][24][25]. The study population was followed up from baseline (the date of the second health examination between 2013 and 2014) until the date of death, development of hHF, or December 31, 2017, whichever came first.…”
Section: Study Cohort Outcomes and Follow-upmentioning
confidence: 99%
“…Worldwide estimates of numbers of individuals with Type 1 diabetes (T1D) continue to increase [1]. Among other reasons, this is particularly worrisome since adults with T1D have an almost threefold higher mortality compared to the general population, largely due to premature cardiovascular disease (CVD) [2][3][4][5][6][7]. In this respect, even in children and young adults with T1D, there is evidence of cardiac and vascular dysfunction, as supported by the presence of abnormal global myocardial function, stiffening of large arteries, and early atherosclerosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…analyzed the data of 26,026 type 1 diabetes patients in the Scottish nationwide diabetes register during 2005–2007, and found that the contemporary relative risk of coronary heart disease and stroke among type 1 diabetes patients remains exceptionally high when compared with the general population, although the absolute incidence of CVD was lower than previously reported. In East Asia, Lee et al 2 . analyzed the Korean health insurance data, and reported that the incidence of myocardial infarction and the rate of hospitalization for heart failure were even higher than those of type 2 diabetes patients.…”
Section: Dcct/edic Pittsburg Edc Swedish Ndrmentioning
confidence: 99%